Inflammatory production of reactive oxygen species by Drosophila hemocytes activates cellular immune defenses - Myers, Amber L.; Harris, Caitlin M.; Choe, Kwang-Min; Brennan, Catherine A. (Biochemical and biophysical research communications, 2018)
The production of reactive oxygen species (ROS) is a prominent response to infection among innate immune cells such as macrophages and neutrophils. To better understand the relationship between antimicrobial and regulatory functions of blood cell ROS, we have characterized the ROS response to infection in Drosophila hemocytes. Using fluorescent probes, we find a biphasic hemocyte ROS response to bacterial infection. In the first hour, virtually all hemocytes generate a transient ROS signal, with nonphagocytic cells including prohemocytes and crystal cells displaying exceptionally strong responses. A distinct, and more delayed ROS response starting at 90 min is primarily within cells that have engulfed bacteria, and is sustained for several hours. The early response has a clear regulatory function, as dampening or intensifying the intracellular ROS level has profound effects on plasmatocyte activation. In addition, ROS are necessary and sufficient to activate JNK signalling in crystal cells, and to promote JNK-dependent crystal cell rupture. These findings indicate that Drosophila will be a promising model in which to dissect the mechanisms of ROS stimulation of immune activation. •Biphasic hemocyte ROS response to infection in flies.•Early response high in non-phagocytic prohemocytes and crystal cells.•Delayed ROS in phagocytic cells.•ROS activate plasmatocyte spreading and adhesion.•ROS promote JNK-dependent crystal cell rupture.